Self-reported mental health outcomes of International medical graduates in Australia: a cross-sectional survey - Healey, Sunita Joann Rebecca; Fakes, Kristy; Malau-Aduli, Bunmi S.; Leigh, Lucy; Nair, Balakrishnan R. (Frontiers in Medicine, 2025)
IntroductionInternational medical graduates are an important migrant workforce with unique challenges which may compound mental health outcomes. We examined the rates of self-reported wellbeing, psychological distress and burnout by IMGs in Australia by undertaking a cross-sectional survey of IMGs.MethodsIn late 2023, an online survey of three validated self-reporting mental health instruments was distributed non-randomly to IMGs across Australia, to identify symptoms of wellbeing, likelihood of psychological distress, and burnout.ResultsOf the 286 participants who started the survey, 199 completed the Wellbeing instrument, 191 completed the Kessler (K6) instrument, and 181 completed the Burnout instrument. The calculated wellbeing mean score of participants was 54.6/100 [SD 23.18; median score: 80/100 (27 participants); range: 0–100]. 30/191 (15.7%) participants recorded a K6 score between 19 and 30, indicating a high likelihood of serious psychological distress. 84/181 (46.4%) participants recorded a score indicating some level of burnout. Statistically significant associations (p < 0.001) between ‘Wellbeing’ and ‘Burnout’ versus “Discrimination experienced in the last 5 years” were identified.DiscussionIMGs may be at risk of poor mental health outcomes resulting from their unique experiences, including perceived discrimination. Further exploration in larger and more robust studies is recommended to confirm preliminary findings and address challenges faced by this important migrant workforce.